Respon Inseminator terhadap Penerapan Transfer Embrio di Kabupaten Lampung Tengah, Provinsi Lampung - G Vivi; R Noviadi; T Rumiyani (Politeknik Negeri Lampung, 2021)
Efforts to apply embryo transfer reproductive technology to community breeders in Lampung Tengah Regency involve inseminators who have an interest and influence in the success of embryo transfer. This study aims to analyze the inseminator response to the implementation of embryo transfer in Lampung Tengah Regency by looking at the influence of age (X1), education level (X2), work experience (X3), knowledge (X4), means of transportation (X5), and facilities and infrastructure (X6) owned by the inseminator of the inseminator's response to the application of embryo transfer in Lampung Tengah Regency. The analytical method used is simple linear regression analysis of 28 inseminators on duty in Lampung Tengah Regency. The results showed that the more productive the inseminator age (old), the lower the inseminator response. Meanwhile, the level of education, work experience, knowledge, means of transportation, and facilities and infrastructure owned by the inseminator in Lampung Tengah did not have a significant positive effect on the inseminator's response regarding the implementation of embryo transfer in Lampung Tengah Regency, Lampung Province.